Analysis of Economic Growth, Unemployment, and Education Level on Poverty in Gresik Regency - Huda, Syamsul; Anik Yuliati (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine how economic growth, the open unemployment rate, and average years of schooling impact poverty levels in Gresik Regency during the period from 2013 to 2022. Utilizing a quantitative methodology, the research relies on secondary data obtained from the Central Bureau of Statistics (BPS) and conducts panel data regression analysis using EViews version 13. The results reveal that economic growth has a positive but statistically insignificant effect on poverty, suggesting that the advantages of growth are not equally shared across various social groups. Conversely, the open unemployment rate significantly and positively influences poverty, indicating that rising unemployment is associated with higher poverty levels. Additionally, the average years of schooling exert a significant negative effect, highlighting the important role of education in reducing poverty by improving individuals’ skills and their competitiveness in the labor market.